2006
DOI: 10.1111/j.1365-2710.2006.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic parameters of vancomycin in critically ill patients

Abstract: The use of population-specific pharmacokinetic parameters and Bayesian forecasting improves dosage-regimen design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
73
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 27 publications
17
73
5
1
Order By: Relevance
“…In this cohort of patients over 80, the best structural model was found to be a two-compartment model, as in most of the studies carried out in adults (9,(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 90%
“…In this cohort of patients over 80, the best structural model was found to be a two-compartment model, as in most of the studies carried out in adults (9,(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, it cannot be assumed that the outcomes from that study would be applicable to ICU patients undergoing CVVHD, because of the wide variability in the pharmacokinetics of vancomycin in these patients and the differences in types of dialysis. 43,44 However, the results of the current study for initial intermittent dosing of 1.25-1.5 g IV q24h in critically ill patients undergoing CVVHD fall within the range recommended by Joy and others. 16 In the investigation by Davies and others, 17 4 ICU patients were managed with concurrent vancomycin and CVVHD.…”
Section: -41mentioning
confidence: 77%
“…Previous studies have demonstrated that there are significant changes in both clearance and volume of distribution throughout the course of vancomycin therapy in ICU patients. [42][43][44] del Mar Fernández and others 44 observed that the mean volume of distribution of vancomycin among 46 critically ill patients was 1.69 L/kg, nearly double that observed in healthy adult subjects with normal renal function (0.4-1 L/kg). 30,[45][46][47] In a population-based = area under the concentration-time curve over 24 h, MIC = minimum inhibitory concentration.…”
Section: -41mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its nephrotoxic effects, empirical dosing based on creatinine clearance with subsequent TDM of C min plasma concentrations is recommended. 29 …”
Section: Glycopeptidesmentioning
confidence: 99%